Emergence and Evolution of Islamic Culture and Civilization in Kashmir: An Analytical and Historical Overview - Muhammad Tayyab Khan; Dr Hafiz Muhammad Arshad Iqbal (Al Basirah, 2020)
From the Kashmiri ruler Rinchana (1320- 1323 A.D)‟s embracing Islam by a Sufi saint Sayyid Sharaf-ud-Din Abdul Rahman (popularized to Bulbul Shah)(1326 A.D.), one can derive that it is a dramatic scene that the king of a time became a figure of an Islamic civilization at once but actually with the long background of Muslims‟ commencement in the state and its adjacent and king‟s discontent regarding other religions of the state led him to accept the rapidly spreading Islamic civilization. King‟s debate with the scholars of all ongoing religions of Kashmir and preferring Islam as a religion among the other religions marks his adoption of a new civilization more significant and remarkable. Being a multicultural and multi religious nature of the state, Islamic civilization and culture observe many pros and cons during the centuries in Kashmir. It took more than half century to stand on its feet. It faced many internal and external challenges but it was survived and resuscitated. Irani Sufi saint Syed Ali Hamdani(1384 C.E) and his followers played a vital role to nurture Islamic civilization and its manifestation to an extent that once Kashmir was considered the central part of Islamic culture and civilization and that was in the era of great Sultan Zain ul Abideen(1420- 1470) known as Bud Shah(great shah), as his period witnessed abundant developments in art, languages, translations in Persian, Arabic from Sanskrit and vice versa and many other sciences. Although the Salateen‟s era(1339-1560) was the climax of Islamic culture and civilization in Kashmir but the situation during the other eras like of Chaks (1560-1586 C.E), Mughuls (1586-1752 C.E), Afghans(1752- 1819) Sikhs(1819-1846), Dogras (1846-1947) and modern time(1947 to till date) is still remarkable as many developments regarding various sciences, arts and languages were witnessed. The study endeavors to explore the background of the commencement of Islamic culture and civilization and its evolution and how did Kashmiri people respond to new developments and how did they resuscitate while facing the various challenges through the centuries.